2004
DOI: 10.1113/jphysiol.2003.056887
|View full text |Cite
|
Sign up to set email alerts
|

Does gender affect human pulmonary gas exchange during exercise?

Abstract: Womenmayexperiencegreaterpulmonarygasexchangeimpairmentduringexercisethanmen.To test this we used the multiple inert gas elimination technique to study eight women and seven men matched for age, height andV O 2 max (∼48 ml kg −1 min −1 ) during normoxic and hypoxic (inspiredP O 2 = 95 Torr) cycle exercise. Resting lung function was similar between the sexes, except for a lower carbon monoxide diffusing capacity (DL CO ) in women (P < 0.05). Arterial P O 2 ,P CO 2 and alveolar-arterial O 2 difference (A−aD O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 33 publications
6
60
1
3
Order By: Relevance
“…There do not appear to be gender differences in the age range 6 to 18 years (214). It has been suggested that women may be more susceptible to impaired pulmonary gas exchange during exercise than height-matched men, because women have smaller lung volumes, lower maximal expiratory flow rates, and smaller diffusion surface areas resulting in reduced O 2 -diffusing capacity (101,223,269). If CO 2 -diffusing capacity is similarly reduced, this may result in an increased susceptibility to respiratory acidosis under conditions of moderate-intensity exercise.…”
Section: Gendermentioning
confidence: 96%
See 1 more Smart Citation
“…There do not appear to be gender differences in the age range 6 to 18 years (214). It has been suggested that women may be more susceptible to impaired pulmonary gas exchange during exercise than height-matched men, because women have smaller lung volumes, lower maximal expiratory flow rates, and smaller diffusion surface areas resulting in reduced O 2 -diffusing capacity (101,223,269). If CO 2 -diffusing capacity is similarly reduced, this may result in an increased susceptibility to respiratory acidosis under conditions of moderate-intensity exercise.…”
Section: Gendermentioning
confidence: 96%
“…If CO 2 -diffusing capacity is similarly reduced, this may result in an increased susceptibility to respiratory acidosis under conditions of moderate-intensity exercise. The possible impairment was systematically studied using the multiple inert gas elimination technique in eight women and seven men matched for age, body fat (mean and women were lean-less than 20% body fat), height, andVo 2max during normoxic and hypoxic (inspired Po 2 = 95 mmHg) cycle exercise (223). In women, compared to men, there was a tendency for VCO 2 to be lower and respiratory exchange ratio (RER) was lower; however, there was no difference in the ventilatory equivalent for CO 2 (V E /VCO 2 ).…”
Section: Gendermentioning
confidence: 99%
“…These sex-related differences in the respiratory system persist after adjustment for body dimensions, which has been referred to as a ''dysanapsis'', or unequal growth of the lung parenchyma and bronchial tree with respect to body size. However, smaller lungs at any given body size do not affect gas exchange [6] and, if anything, would increase rather than decrease pulmonary vascular resistance. The control of breathing is also different in women, with progesterone-dependent, increased peripheral chemosensitivity [7], which results in in slightly but significantly lower arterial partial pressure of carbon dioxide [8].…”
Section: Sex Matters In Pulmonary Arterial Hypertensionmentioning
confidence: 95%
“…The drop in PaCO2 is about 5 to 6 mmHg (from a resting value of 38 -40 mmHg to a peak exercise value of 34 mmHg). [1][2][3] In contrast, evidence suggests that subjects with extreme obesity (BMI 40 kg/m 2 ) maintain PaCO2 from rest to peak exercise. 4,5 A PaCO2 35.0 mmHg during strenuous exercise suggests poor compensatory exercise hyperventilation, and PaCO2 38.0 mmHg suggests absence of a complete hyperventilatory response.…”
mentioning
confidence: 99%
“…If PaCO2 does not decrease between rest and peak exer-cise, there may still be some issues with breathing, as normal individuals do have a reduction in PaCO2 of 5 to 6 mmHg between rest and maximal exertion. [1][2][3] About 75% of individuals with extreme obesity have a PaCO2 35.0 mmHg at peak exercise despite arterial plasma lactate (a breathing stimulant) levels of 8.0 mmol/L. 4 This demonstrates that most individuals with extreme obesity have a "poor breathing response" to strenuous, near maximal exercise that is likely mechanical in nature.…”
mentioning
confidence: 99%